A Case Series of COVID-19 with Severe ARDS and Comorbidities who Survived without Invasive Mechanical Ventilation in ICU at Wisma Atlet Kemayoran COVID-19 Field Hospital, Jakarta - Made Yudha Asrithari Dewi; Ahmad Irfan (Jurnal Anestesi Perioperatif, 2021)
Sebagian besar orang yang terinfeksi COVID-19 asimtomatis ataupun bergejala ringan. Namun tidak sedikit juga yang mengalami acute respiratory distress syndrome (ARDS), membutuhkan perawatan ICU bahkan berakhir dengan kematian. Indonesia bahkan telah melampaui angka dunia dengan angka 2,7%. Keadaan ini lebih berisiko dialami oleh pasien dengan komorbid seperti hipertensi (50,1%), diabetes (36,6%), dan obesitas (13,3%). Kebutuhan terapi oksigen dengan ventilasi mekanik hingga tindakan intubasi meningkat pada kebanyakan kasus dengan komorbid. Serial kasus ini melaporkan dua pasien terkonfirmasi COVID-19 dengan komorbid yang memenuhi kriteria intubasi, namun tidak dilakukan. Dalam perjalanannya kedua kasus mengalami perbaikan klinis dan sembuh. Beberapa kemungkinan yang dapat dijelaskan, yaitu terdapat perbedaan antara ARDS pada COVID-19 (CARDS) dan ARDS klasik. Selain itu, prone position yang membantu meningkatkan oksigenasi dan mengatasi hipoksemia melalui beberapa mekanisme. Penggunaan HFNC dini pada pasien COVID-19 dan pemberian regimen kombinasi terapi antibiotik, antivirus, antikoagulan, serta antiinflamasi dinilai dapat menurunkan morbiditas pasien. Tujuan penanganan ARDS ialah menangani hipoksemia dengan meningkatkan oksigenasi. Selain dengan pemberian terapi oksigen untuk meningkatkan FiO2, dapat juga dilakukan dengan prone position. Prone position pada kasus dengan kombinasi HFNC dinilai berhasil karena pasien mampu bertahan tanpa penggunaan ventilasi mekanik dan mengalami perbaikan klinis hingga sembuh. Two Reported Cases of COVID-19 with Severe ARDS and Comorbidities who Survived without Invasive Mechanical Ventilation in ICU at Wisma Atlet Kemayoran COVID-19 Field Hospital, JakartaMost patients with COVID-19 are either asymptomatic or have mild symptoms. However, many also experience acute respiratory distress syndrome (ARDS), requiring ICU, or even lead to death. Indonesia’s case fatality rate of 2.7% has exceeded the global case. Patients with comorbidities such as hypertension (50.1%), diabetes (36.6%), and obesity (13.3%) are at higher risk of experiencing this situation. The need for oxygen therapy with mechanical ventilation or even intubation is increased in most cases with previously mentioned comorbidities. These serial cases reported two confirmed COVID-19 patients with comorbidities that fulfilled intubation criteria; however, the intubation procedures were not performed. Both cases experienced clinical improvement and improved throughout the treatment period. Several possible explanations include that there are differences between ARDS in COVID-19 (CARDS) and classic ARDS. Moreover, the prone position helps in increasing oxygenation and reducing hypoxemia through several mechanisms. Early HFNC in COVID-19 patients and treatment regimen consisting of antibiotics, antivirus, anticoagulant, and anti-inflammatory drugs are considered to reduce morbidity. The goal of ARDS treatment is to treat hypoxemia by increasing oxygenation. In addition, giving oxygen therapy to increase FiO2 can also be done by prone positioning. Combining prone position and HFNC in these cases was considered successful because the patient were able to survive without the use of mechanical ventilation and experienced clinical improvement until they recovered.